Opaque Layer Firing Temperature and Aging Effect on the Flexural Strength of Ceramic Fused to Cobalt-Chromium Alloy - Oliveira de Vasconcellos, Luis Gustavo [UNESP]; Buso, Leonardo [UNESP]; Lombardo, Geraldo H. L. [UNESP]; Souza, Rodrigo O. A.; Nogueira Junior, Lafayette [UNESP]; Bottino, Marco Antonio [UNESP]; Oezcan, Mutlu (Wiley-Blackwell, 2010)
Purpose: To evaluate the effect of the opaque layer firing temperature and mechanical and thermal cycling on the flexural strength of a ceramic fused to commercial cobalt-chromium alloy (Co-Cr). The hypotheses were that higher opaque layer temperatures increase the metal/ceramic bond strength and that aging reduces the bond strength.Materials and Methods: Metallic frameworks (25 x 3 x 0.5 mm(3); ISO 9693) (N = 60) were cast in Co-Cr and airborne-particle abraded (Al(2)O(3): 150 mu m) at the central area of the frameworks (8 x 3 mm(2)) and divided into three groups (N = 20), according to the opaque layer firing temperature: Gr1 (control)-900 degrees C; Gr2-950 degrees C; Gr3-1000 degrees C. The opaque ceramic (Opaque, Vita Zahnfabrick, Bad Sackingen, Germany) was applied, and the glass ceramic (Vita Omega 900, Vita Zahnfabrick) was fired onto it (thickness: 1 mm). While half the specimens from each group were randomly tested without aging (water storage: 37 degrees C/24 hours), the other half were mechanically loaded (20,000 cycles; 50 N load; distilled water at 37 degrees C) and thermocycled (3000 cycles; 5 degrees C to 55 degrees C, dwell time: 30 seconds). After the flexural strength test, failure types were noted. The data were analyzed using 2-way ANOVA and Tukey's test (alpha = 0.05).Results: Gr2 (19.41 +/- 5.5 N) and Gr3 (20.6 +/- 5 N) presented higher values than Gr1 (13.3 +/- 1.6 N) (p = 0.001). Mechanical and thermal cycling did not significantly influence the mean flexural strength values (p > 0.05). Increasing the opaque layer firing temperature improved the flexural bond strength values (p < 0.05). The hypotheses were partially accepted.Conclusion: Increasing of the opaque layer firing temperature improved the flexural bond strength between ceramic fused to Co-Cr alloy.
Keywords: Metal ceramic alloys; chromium alloys; flexural strength; mechanical cycling; thermocycling